Application of Digital Literacy to Chemistry Learning Outcomes of High School Students - Djarwo, Catur Fathonah; Suaka, Irwandi Yogo; Safitri, Ima Nur; Putri, Intan Mentari (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This research examines the impact of implementing digital literacy on chemistry learning for Muhammadiyah High School students in Jayapura City. In today's digital era, technology plays an important role in education, and digital literacy is an increasingly relevant skill. The data collection technique in this research was carried out using test techniques. The research results show that the use of digital technology in chemistry learning also contributes positively to student learning outcomes. This can be seen in the posttest scores obtained by the average student score of 67.86 in the experimental group and 77.68 in the control group. These findings provide empirical support for the importance of digital literacy in modern education.